Graphene oxide/polysulfone hollow fiber mixed matrix membranes for gas separation - Zahri, K. (Royal Society of Chemistry, 2016)
Hollow fiber mixed matrix membranes (MMM) were fabricated by embedding graphene oxide (GO) into a polysulfone (PSf) polymer matrix to investigate the gas permeation properties of CO2, N2, and CH4 in the membrane. The properties of the neat membrane and MMM loaded with 0.25% of GO were investigated. The transmission electron microscopy (TEM) and atomic force microscopy (AFM) analysis confirmed the synthesized GO was in the nanosheet form. The prepared MMM exhibited an improvement in mechanical and thermal stability. Field emission scanning electron microscopy (FESEM) analysis showed that the addition of GO into the polymer developed a well integrated skin layer as well as change in the formation of a membrane substructure layer which lead to better gas separation performance properties. The unique characteristics of GO which showed a strong affinity towards CO2 has contributed to the increment of CO2 permeance by 14%. Besides, GO created a path for small molecule gases (CO2) and restricted large molecule gases (N2 and CH4) to pass through the membrane. Both CO2/N2 and CO2/CH4 selectivity of MMM were enhanced by 158% and 74% respectively as compared to that of the neat PSf membrane.